Reliability Design of Mechanical Systems A Guide for Mechanical and Civil Engineers - Woo, Seongwoo; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book describes basic reliability concepts - parametric ALT plan, failure mechanism and design, and reliability testing with acceleration factor and sample size equation. A generalized life-stress failure model with a new effort concept has been derived and recommended to calculate the acceleration factor of the mechanical system. The new sample size equation with the acceleration factor has also been derived to carry out the parametric ALT. This new parametric ALT should help a mechanical/civil engineer to uncover the design parameters affecting reliability during the design process of the mechanical system. Consequently, it should help companies to improve product reliability and avoid recalls due to the product/structure failures in the field. As the improper or missing design parameters in the design phase are experimentally identified by this new reliability design method - parametric ALT, the mechanical/civil engineering system might improve in reliability by the increasein lifetime and the reduction in failure rate.
Keywords: Security systems; Mechanical engineering; Civil engineering; Security Science and Technology; Mechanical Engineering; Civil Engineering